Imine modified ZnO nanoparticles: a luminescent chemodosimeter for Al3+ and S2− ions based on ligand displacement reaction. (24th December 2014) - Kaur, Kamaljot; Chaudhary, Savita; Singh, Sukhjinder; Mehta, Surinder Kumar
Abstract : A novel fluorescent chemosensor for rapid recognition of Al 3+ and S 2− ions using imine capped ZnO nanoparticles in aqueous media. Abstract : In light of efficient and facile recognition of ionic species under physiological conditions, coating of a semiconducting nanoparticle surface with functional ligands is emerging as a competent technique. In this work, a new ZnO nanoparticle based probe L has been synthesized and developed as a dual optical chemosensor. Here, successful linkage of Schiff base molecules SB on nanoparticles surface enables modification of its functionality and photophysical signalling abilities for detecting toxic analytes. The fabrication of coated nanoparticles has been well confirmed using IR, CHNS, TEM, UV-vis and fluorescence spectroscopy. Among all the ions investigated, probe L shows high fluorometric selectivity for Al 3+ and S 2− ions with a red shift of 55 nm. The interactions also cause the color change of solution from white to bright yellow. The key finding of the present study is that the nanodosimeter exhibits high selectivity over other competitive ions with a detection limit of 3 and 170 nM for Al 3+ and S 2−, respectively.